1996
DOI: 10.1017/s0960258500003111
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mechanisms of breaking seed dormancy

Abstract: Features of chemicals which break seed dormancy and the mechanisms of their action are discussed with reference to results obtained with red rice (Oryza sativa) and other relevant research. The significance of chemical structure, including the nature and location of functional groups, is considered, and the fact that similar structures can elicit different biochemical responses is illustrated with examples. As yet it is unclear whether changes in cell pH, highly correlated with the uptake of, and metabolism to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…This means that determination of relevant parameters should take place before visible sprouting, but even then it is hard to identify the parameters as dormancy breaking parameters or sprouting parameters. Discussing dormancy of true seeds, Cohn (1996) stated: 'if one desires to increase the chances of successfully identifying events associated with the dormancy breaking process, it is essential to conduct time course studies using chemical pulse treatments applied to a uniform and vigorous seed sample'. Markers for the progression from dormancy to germination processes, i.e.…”
Section: Dormancy Breaking and Sproutingmentioning
confidence: 99%
“…This means that determination of relevant parameters should take place before visible sprouting, but even then it is hard to identify the parameters as dormancy breaking parameters or sprouting parameters. Discussing dormancy of true seeds, Cohn (1996) stated: 'if one desires to increase the chances of successfully identifying events associated with the dormancy breaking process, it is essential to conduct time course studies using chemical pulse treatments applied to a uniform and vigorous seed sample'. Markers for the progression from dormancy to germination processes, i.e.…”
Section: Dormancy Breaking and Sproutingmentioning
confidence: 99%
“…Another disadvantage of the pharmacological approach is that the biochemical response measured may be specific to the chemical challenge rather than a controlling response involved in the dormancybreaking process. Our research (reviewed in Cohn, 1996) has shown that dormancy-breaking chemicals that are closely related structurally may elicit very different metabolic reactions from the seed. Therefore, my own approach in using dormancy-breaking chemicals is to employ a comparative strategy as a control.…”
Section: Choosing Environmental or Chemical Probes To Perturb The Dormentioning
confidence: 99%
“…However, GA application is not the only way to break dormancy experimentally. Many abiotic factors may suffice, such as anaerobiosis, freezing, high temperature, and a range of different chemicals (Cohn, 1996; Rinne et al ., 1997; Shirazi and Fuchigami, 1995; Tanino et al ., 1989; Wisniewski et al ., 1996). The fact that such a wide variety of factors can break dormancy brings into question the existence of universal key components and pathways in dormancy cycling, as well as the validity of existing theories and concepts (Lang, 1987).…”
Section: Introductionmentioning
confidence: 99%